A versatile method for the preparation of carbon–rhodium hybrid catalysts on graphene and carbon black. Issue 3 (22nd December 2015) - Wong, Chin Min; Walker, D. Barney; Soeriyadi, Alexander H.; Gooding, J. Justin; Messerle, Barbara A.
Abstract : A direct and rapid access to highly efficient and recyclable carbon–rhodium hybrid catalysts for the hydrosilylation reaction is presented. Abstract : Strategies for combining the selectivity and efficiency of homogeneous organometallic catalysts with the versatility of heterogeneous catalysts are urgently needed. Herein a direct and modular methodology is presented that provides rapid access to well-defined carbon–rhodium hybrid catalysts. A pre-synthesized Rh(i ) complex containing a carbene-triazole ligand was found to be stable for direct immobilization onto unactivated graphene, carbon black and glassy carbon electrodes. Characterization of the heterogeneous systems using X-ray photoelectron spectroscopy (XPS), thermogravimetric analysis (TGA), inductively coupled plasma-optical emission spectroscopy/mass spectrometry (ICP-OES/MS), Raman spectroscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) confirmed the well-defined nature of the hybrid catalysts. The hybrid catalysts show excellent activity, comparable to that of the homogeneous system for the hydrosilylation of diphenylacetylene, with turnover numbers ranging from 5000 to 48 000. These catalysts are the best reported to date for the hydrosilylation of diphenylacetylene. In common with conventional heterogeneous catalysts, high reusability, due to a lack of Rh metal leaching, was also observed for all carbon–rhodium complexes under investigation.